2016
DOI: 10.2322/tastj.14.pb_47
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fluctuations and Electron Transport in Two-Dimensional Simulations of Hall Thrusters using an Axial-Azimuthal Hybrid Model

Abstract: A two-dimensional model of the Hall thruster with kinetic, non-magnetized ions, and fluid electrons is presented. The model dynamically evolves azimuthal flows and fluctuations, differing from standard hybrid models that assume axisymmetry and resolve quantities in the radial and axial coordinates only. Unlike those descriptions, which typically use adhoc cross-field electron transport parameters in order to sustain the discharge, the present model relies on classical transport and fluctuations generated withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…heat balance and convection) play an important role in such ionization instabilities. For rotating spoke simulations, Lam et al and Fernandez et al have attempted axial-azimuthal simulations using a hybrid model assuming quasineutrality [14,15]. The azimuthal oscillations shown were not as clear as the ones observed in experiment and the authors reported that the simulations were not stable after a given period.…”
Section: Introductionmentioning
confidence: 99%
“…heat balance and convection) play an important role in such ionization instabilities. For rotating spoke simulations, Lam et al and Fernandez et al have attempted axial-azimuthal simulations using a hybrid model assuming quasineutrality [14,15]. The azimuthal oscillations shown were not as clear as the ones observed in experiment and the authors reported that the simulations were not stable after a given period.…”
Section: Introductionmentioning
confidence: 99%